2011
DOI: 10.1080/10286020.2011.554828
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of bilobol and adipostatin A

Abstract: Concise total synthesis of bilobol 5-pentadecenylresorcinol (1), isolated from Gingko biloba fruits, has been achieved in 10 steps with 51% overall yield from 3,5-dihydroxybenzoic acid (3). Adipostatin A (2), isolated from the fruits as well as from Streptomyces cyaneus 2299-SV1, has also been synthesized in two steps from methylated bilobol (10). The structure-activity relationship study of synthetic products was described by means of cytotoxic assay against human KB carcinoma cell lines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…Of which, C13:0 and C15:0 were found to exert the greatest inhibitory effects in both cancer cells (IC 50 s: 15.12 μM for C13:0 and 14.84 μM for C15:0 in HCT‐116; and IC 50 s: 24.86 μM for C13:0 and 25.50 μM for C15:0 in HT‐29) . ARs C15:0 and C15:1 have also been shown to be cytotoxic against human KB carcinoma cell lines . In addition, our efforts led to the discovery of a series of oxyphytosterols from WB, and our results demonstrated that oxyphytosterols could significantly suppress the growth of human colon cancer cells through the apoptosis pathway, with IC 50 values ranging from 15.73 to 41.91 μM for HCT‐116 and from 10.09 to 60.46 μM for HT‐29 .…”
Section: Health‐promoting Effects Of Wheat Phytochemicalsmentioning
confidence: 88%
“…Of which, C13:0 and C15:0 were found to exert the greatest inhibitory effects in both cancer cells (IC 50 s: 15.12 μM for C13:0 and 14.84 μM for C15:0 in HCT‐116; and IC 50 s: 24.86 μM for C13:0 and 25.50 μM for C15:0 in HT‐29) . ARs C15:0 and C15:1 have also been shown to be cytotoxic against human KB carcinoma cell lines . In addition, our efforts led to the discovery of a series of oxyphytosterols from WB, and our results demonstrated that oxyphytosterols could significantly suppress the growth of human colon cancer cells through the apoptosis pathway, with IC 50 values ranging from 15.73 to 41.91 μM for HCT‐116 and from 10.09 to 60.46 μM for HT‐29 .…”
Section: Health‐promoting Effects Of Wheat Phytochemicalsmentioning
confidence: 88%
“…[ 60 61 ] Bilobalides are sesquiterpenes closely related to ginkgolides, but differ from ginkgolides by the absence of tetrahydrofuran ring, while bilobol plays a role in stress tolerance. [ 62 ] Tree gender, stage of development, age, soil, and natural variability due to the allogamous status of plant species all lead to great diversity in terpene content, but tree age is a major determinant of this content in different ways. [ 63 ] Diurnal, seasonal, and climatic factors affect biosynthesis and the resultant yield.…”
Section: Importance and Phytochemistrymentioning
confidence: 99%
“…[ 51 78 ] Further, the leaves and sarcotesta contain ginkgolic acid and long-chain alkylphenols bilobol or cardol. [ 62 79 ] A toxin 4-0-methyl-pyridoxine, the mechanism of action of which is to antagonize the activity of vitamin B6, is produced by raw ginkgo nuts. [ 80 ] Phytochemicals such as rutin, quercetin and kaempferol are known to be genotoxic, but yet, there are no indepth studies on the carcinogenic effect of these phytochemicals that are isolated from ginkgo leaf extract.…”
Section: Importance and Phytochemistrymentioning
confidence: 99%
“…It has been demonstrated that upon feeding G. biloba to Spodoptera littoralis, significant differential levels of quercetin and kaempferol were observed, compared to mechanically damaged G. biloba (Mohanta et al, 2012). Tanaka et al (2011) reported the role of bilobol and found that it plays significant role in plant stress response. Cell cultures of G. biloba with biotic elicitors Candida albicans resulted in enhanced accumulation of bilobalide and ginkgolide as compared to control.…”
Section: Role Of Ginkgo Biloba Metabolite Upon Different Stress Condimentioning
confidence: 99%